2021
DOI: 10.1016/j.jinf.2021.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 preventive measures on other infectious and non-infectious respiratory diseases in Pakistan

Abstract: Impact of COVID-19 preventive measures on other infectious and non-infectious respiratory diseases in PakistanDear Editor , Authors contributionsMSR, AI, MMA, MU, MS and SSZZ conceived and designed the study. MSR, MU, MMA were responsible for data collection and analysis. MSR, MU and MMA wrote the manuscript draft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…Besides influenza, studies show a meaningful reduction in the activity and reported cases of other respiratory germs such as Mycobacterium tuberculosis, pneumonia, rhinovirus, enterovirus, adenovirus, and several other respiratory infectious diseases mentioned in Table 1 [ 5 , 19 , 20 , 22 , 25 , 26 , 29 ]; however, many of them are scarcely investigated. For example, measles cases in Taiwan were reported to be zero after the pandemic, possibly owing to the implemented precautions during the pandemic [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides influenza, studies show a meaningful reduction in the activity and reported cases of other respiratory germs such as Mycobacterium tuberculosis, pneumonia, rhinovirus, enterovirus, adenovirus, and several other respiratory infectious diseases mentioned in Table 1 [ 5 , 19 , 20 , 22 , 25 , 26 , 29 ]; however, many of them are scarcely investigated. For example, measles cases in Taiwan were reported to be zero after the pandemic, possibly owing to the implemented precautions during the pandemic [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma pneumonia. Bordetella pertussis 20 Rana [ 26 ] Letter to the editor Pakistan Data based on the surveillance records available at NIH Islamabad. Data for non-infectious respiratory diseases obtained from the chest care clinic Islamabad, 2019–2020 * * * * RSV, measles, rubella, pertussis, diphtheria, EBV, H. influenza, VZV 21 Sakamoto [ 8 ] Research Japan Data obtained from the National Institute of Infectious Diseases Japan from 5000 sentinel centers between 2014 and Mar 15th, 2020 * 22 Singh [ 27 ] Brief report USA (Wisconsin) Data from 2015–2020 retrieved from academic health system laboratory in southeastern Wisconsin * 23 Soo [ 28 ] Cross-sectional Singapore Routine sentinel surveillance data on ILI from a national network of primary care clinics and the National Public Health Laboratory, comparison of influenza activity between epidemiologic weeks 1–4 and weeks 5–9 of 2020 Vs. 2016–2019 * 24 Tan [ 29 ] Letter to the editor Singapore Laboratory confirmed (16-target PCR on oropharyngeal specimen) community-onset respiratory viruses that were admitted to Singapor...…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that several infectious diseases, such as influenza and tuberculosis, were collaterally reduced during the COVID-19 pandemic. For instance, the overall number of twelve notifiable infectious diseases and five non-infectious respiratory diseases in Pakistan declined by 52 •3% in 2020 [6] . A similar reduction was found for seasonal influenza in Japan [7] and tuberculosis in Jiangsu, China [8] .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there has not been any work that has demonstrated the positive effect of preventive measures on COVID-19. In contrast, a study in Pakistan showed that the application of protective measures dramatically reduces the risk of other respiratory diseases [130] Recently a Japanese study focused only on wearing a mask as a measure and they found that for a sample of 820 individuals, mask users were infected at a rate of 0.4 times that of those who did not wear masks [131] demonstrating the importance of this measure. Our findings provide novel insights into the role of personal protective measures on the spread of infection and symptom severity.…”
Section: Discussionmentioning
confidence: 99%